Cyto-diagnosis of unilateral adrenal histoplasmosis mimicking a primary adrenal neoplasm in an immunocompetent patient - Negi, Lalita; Sharma, Sudarshan; Mardi, Kavita; Sood, Shivani; Negi, Rajender (International Journal of Research in Medical Sciences, 2025)
Histoplasmosis mostly shows bilateral adrenal gland involvement in immunocompromised patients. Our case is of a 43 years old immunocompetent male patient having pain in the left flank for one month. CECT abdomen revealed a well-defined hypodense mass measuring 64×61×56 mm with necrotic areas in right adrenal region. A possibility of primary adrenal neoplasm was suggested. Left side adrenal gland was normal. Microscopic examination of imprint smears from adrenal mass revealed cellular smears revealing histiocytes, plasma cells, lymphocytes and numerous intra-cytoplasmic and extra-cytoplasmic yeast forms with basophilic crescent shaped nucleus with pericellular halo. Background showed RBC’s, acellular debris and multinucleate giant cells. Diagnosis of histoplasmosis was suggested which was confirmed on histopathology and culture. Patient recovered with anti-fungal treatment. If Fine needle aspiration (FNA) of the adrenal mass would have been done, adrenalectomy could be prevented. This case highlights the importance of FNA in diagnosing abdominal lumps and avoiding unnecessary surgery.